2023
DOI: 10.1038/s41598-023-29125-7
|View full text |Cite
|
Sign up to set email alerts
|

Compositional changes and ecological characteristics of earthworm mucus under different electrical stimuli

Abstract: Earthworm mucus is rich in nutrients that can initiate the mineralization and humification of organic matter and is of great importance for contaminated soil remediation and sludge reutilization. In this study, six voltage and current combinations were utilized to promote earthworm mucus production (5 V and 6 V at 10, 20 and 30 mA, respectively), to explore the compositional changes of the mucus produced under different electrical stimuli, and to propose the best electrical stimulation group and mucus fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Many studies electrically or chemically stimulate earthworms to release exudate in order to collect and study mucus (Jiang et al, 1990; Zhang et al, 2016), and E. fetida excretes small amounts of exudate proteins under basal conditions (Rivera et al, 2020; Heredia et al, 2008). The most recent research in the field has shown that exudate produced in response to varying intensities of electrical stimuli differ in pH and concentration of amino acids, nitrogen, potassium, and phosphorus (Huan et al, 2023). Our transcriptome data suggest that homologs to secreted CAVI may be one component of both exudate and mucus (Figure 2, S1, transcript ID: 67832_c1_g1_i5 & 76341_c1_g1_i1, 76341_c1_g1_i17).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies electrically or chemically stimulate earthworms to release exudate in order to collect and study mucus (Jiang et al, 1990; Zhang et al, 2016), and E. fetida excretes small amounts of exudate proteins under basal conditions (Rivera et al, 2020; Heredia et al, 2008). The most recent research in the field has shown that exudate produced in response to varying intensities of electrical stimuli differ in pH and concentration of amino acids, nitrogen, potassium, and phosphorus (Huan et al, 2023). Our transcriptome data suggest that homologs to secreted CAVI may be one component of both exudate and mucus (Figure 2, S1, transcript ID: 67832_c1_g1_i5 & 76341_c1_g1_i1, 76341_c1_g1_i17).…”
Section: Discussionmentioning
confidence: 99%
“…Earthworm (a common invertebrates in soil) could secrete a mixture of proteins, amino acids, carbohydrates, fatty acids, and polysaccharides from their body surface during movement (Huan et al, 2023). They can enter the rhizosphere and interact with ENMs.…”
Section: Role Of Res On the Transformation Of Enmsmentioning
confidence: 99%
“…Many studies electrically or chemically stimulate earthworms to release exudate in order to collect and study mucus (Jiang et al, 1990;Zhang et al, 2016), and E. fetida excretes small amounts of exudate proteins under basal conditions (Heredia Rivera et al, 2020;Heredia et al, 2008). The most recent research in the field has shown that exudate produced in response to varying intensities of electrical stimuli differ in pH and concentration of amino acids, nitrogen, potassium, and phosphorus (Huan et al, 2023). Our transcriptome data suggest that homologs to secreted CAVI may be one component of both exudate and mucus (Figure 2, S1, transcript ID: 67832_c1_g1_i5 and 76341_c1_g1_i1, 76341_c1_g1_i17).…”
Section: Co 2 Adaptationsmentioning
confidence: 99%